The real crash : America's coming bankruptcy--how to save yourself and your country - Schiff, Peter D., 1963- (St. Martin's Press, 2012)
Predicts a worse crash if key economic changes cannot be made, arguing that American consumer habits are at the heart of today's problems and recommends that the nation declare bankruptcy and rebuild broken systems from scratch.